Neuroprotective effect of ethanolic leaf extract of Commiphora caudata (Wight & Arn) against lipopolysaccharide-induced neurotoxicity in Wistar rats - Ponmalai Srinivasan; Balasubramanian Arul; Ramalingam Kothai (Shahrekord University of Medical Sciences, 2021)
Introduction: Commiphora caudata contains various essential phytoconstituents and is a potential medicinal plant used traditionally to treat various ailments such as neurodegenerative diseases. The present study aimed to evaluate the neuroprotective effect of ethanolic leaf extract of Commiphora caudata against the lipopolysaccharides (LPS) induced behavioral changes in rats. Methods: The in-vitro antioxidant potential was evaluated by 1-diphenyl-2-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assay methods. For in-vivo studies, the animals were pre-treated with ethanolic leaf extract of Commiphora caudata (EECC) at 200 and 400 mg/kg of b.w for 30 days, and neurotoxicity was induced with a single intraperitoneal injection of LPS 1 mg/kg, b.w on day 31. The neurotoxicity was evaluated with a chain of behavioral tests such as the Morris water maze test, radial arm maze, and choice reaction time (CRT) tests. At the end of the study, rats were sacrificed, the brain hippocampal region was removed, and the levels of acetylcholinesterase, nitric oxide, and protein were measured. Results: The IC50 value in the DPPH method was 71.58 ± 15.62 μg, and the total antioxidant activity of EECC was found to be 742.33 ± 14.57 μmol Fe (II)/g extract. In behavioral tests, animals treated with EECC at 200 and 400 mg/kg showed a neuroprotective effect in the Morris water maze test, an 8-arm radial maze test, and in the CRT test. Both doses reduced acetylcholinesterase, nitric oxide, and protein levels (P < 0.001), respectively. Conclusion: The present study results showed the promising neuroprotective effects of ethanolic extract of leaves of Commiphora caudata and its action against the LPS-induced cognitive impairment in rats.